HUBUNGAN PENGETAHUAN DAN SELF-EFFICACY MAHASISWA KEPERAWATAN DENGAN KEMAUAN MELAKUKAN RJP SELAMA PANDEMI - Sanaya Azizah Puteri (2021)
Cardiopulmonary resuscitation (CPR) is an essential emergency procedure done to patients with cardiac and respiratory arrest. A good quality CPR could improve survival rate and lessen neurological impacts. Shifting from a normal situation to being in the middle of a pandemic could affect willingness to perform CPR. This study was conducted to analyze the correlation between nursing students' knowledge, self-efficacy, and willingness to perform CPR during pandemic. Cross Sectional design and simple random sampling method were used with 158 samples participating in this study. Data was collected using questionnaires consisting of three parts; CPR knowledge, resuscitation self-efficacy scale (RSES), and willingness to perform CPR. Statistical results show that there is no significant correlation between CPR knowledge and willingness to perform CPR during a pandemic (p = 0,337 for CPR on family members and p = 0,610 for CPR on strangers). However, significant correlation between CPR self-efficacy and willingness to perform CPR during pandemic was found (p = 0,016 for CPR on family members and p = 0,035 for CPR on strangers).